Collagen deposition in lung parenchyma driven by depletion of interstitial Lyve-1+ macrophages prevents cigarette smoke-induced emphysema and loss of airway function - Dagnachew, Yinebeb Mezgebu; Lim, Hwee Ying; Wupeng, Liao; Lim, Sheau Yng; Lim, Sheng Jie Natalie; Thiam, Chung Hwee; Tan, Shu Wen; Eng, Joan Lau Joo; Mei, Dan; Hazwany Mohammad Azhar, Syaza; Ong, Wei Siong; Tan, Qi Hui Caris; et al. (Frontiers in Immunology, 2025)
IntroductionCollagen is essential for maintaining lung structure and function and its remodeling has been associated with respiratory diseases including chronic obstructive pulmonary disease (COPD). However, the cellular mechanisms driving collagen remodeling and the functional implications of this process in the pathophysiology of pulmonary diseases remain poorly understood.MethodsTo address this question, we employed Lyve1wt/cre; Csf1rflox/flox mice with specific depletion of Lyve-1+ macrophages and assessed the content, types and organization of collagen in lung compartments at steady state and after chronic exposure to cigarette smoke (CS).ResultsUsing this mouse model, we found that the absence of this subpopulation of tissue resident macrophage led to the deposition of type I collagen fibers around the alveoli and bronchi at steady state. Further analysis by polarized light microscopy and Sircol collagen assay revealed that the collagen fibers accumulating in the lungs depleted of Lyve-1+ macrophages were thicker and crosslinked. A decrease in MMP-9 gene expression and proteolytic activity together with an increase in Col1a1, Timp-3 and Lox expression accompanied the collagen alterations. Next, we investigated the effect of the collagen remodeling on the pathophysiology of COPD and airway function in mice lacking Lyve-1+ macrophages exposed chronically to cigarette smoke (CS), a well-established animal model of COPD. We found that deposition of collagen prior CS exposure protected these mice against destruction of alveoli (emphysema), and bronchi thickening and prevented loss of airway function.DiscussionThus, we uncover that interstitial Lyve-1+ macrophages regulate the composition, amount, and architecture of collagen network in the lungs at steady state and that such collagen remodeling functionally impacts the development of COPD. This study further supports the potential of targeting collagen as promising approaches to treat respiratory diseases.